Effects of creatine supplementation on body composition and renal function in rats - Ferreira, Larissa Gorayb [UNIFESP] (2005)
Background: the aim of the present study was to evaluate the long-term effects of oral creatine supplementation on renal function and body composition (fat and lean mass) in an experimental model. Methods: Male Wistar rats were supplemented with creatine (2 g(.)kg(-1) of food) for 10 wk in combination with treadmill exercise, 12 m(.)min(-1), 1 h(.)d(-1) (CREAT+EX, N = 12) or not (CREAT, N = 10), and compared with exercised animals without creatine supplementation (EX, N = 7) and CONTROL animals, N = 7. Body composition and bone mineral density (BMD) were determined by dual x-ray absorptiometry and glomerular filtration rate (GFR) and renal plasma flow (RPF) were measured by inulin and paraaminohippurate clearance, respectively. Results: At the end of the study (post), CREAT+EX presented higher lean mass and lower fat mass than CREAT, EX or CONTROL (349.7 +/- 19.7 vs 313.3 +/- 1- 20.3, 311.9 +/- 30.8, 312.4 +/- 21.0 g and 5.7 +/- 2.3 vs 10.0 +/- 3.3, 9.8 +/- 1.5, 10.0 +/- 3.5%, P < 0.05, respectively). Post lean/fat mass ratio was higher than baseline only in CREAT+EX (18.9 +/- 7.2 vs 8.6 +/- 1.8,P < 0.05). Post BMD was significantly higher than baseline in all groups. GFR and RPF were lower in CREAT versus CONTROL (0.5 +/- .1 vs 1.0 +/- 0.1 and 1.5 +/- 0.2 vs 2.4 +/- 0.5 mL(.)min(-1), P < 0.05, respectively). Conclusion: Creatine supplement in combination with exercise increased the proportion of lean mass more than EX or CREAT alone. the use of creatine alone induced an important and significant reduction of both RPF and GFR.